Privilege or Concession: The Modern Tax Adviser’s Challenge - Castelyn, Donovan; Morgan, Annette; Pinto, Dale (2019)
The gap between legal and non-legal advice, particularly in the context of taxation matters, continues to be truncated through the advent of technological advancements and industrial developments. In the Australian context, a litany of professional advisers and groups are capable of providing taxpayers with tax advice. Broadly, these advisers operate within either the accounting or legal profession and offer similar, if not identical, services. This article explores the relative merits of the privileges or concessions afforded by professional advisers to their clients, and in so doing, advocates for the abrogation of any distinctions in favour of the enactment of a separate statutory tax advice privilege.